Implementation of Aqad Musyarakah Mutanaqisah (MMQ) Take Over Financing on KPR Products in Sharia Banks - Muhammad Rafi Ashsiddiqqy; Hilda Monoarfa; Aneu Cakhyaneu (Review of Islamic Economics and Finance (RIEF), 2020)
Abstract.     House Ownership Financing (PKR) has various types of contracts used, one of which is Musyarakah Mutanaqisah (MMQ). However, financing through the Mushanaqishah Mutanaqishah pattern (MMQ) has some common problems in the banking world faced. This study aims to see how the implementation of the Musharaka Mutanaqishah (MMQ) contract. Take Over financing on KPR products is following Fatwa DSN MUI Number: 73 / DSN-MUI / XI / 2008 concerning Musyarakah Mutanaqisah (MMQ).This study uses a descriptive quantitative method. The population in this study were mortgage customers totaling 31 people with census techniques. The instrument in this study used a questionnaire. The results showed the implementation of the Musyarakah Mutanaqisah (MMQ)  agreement. Take Over financing for KPR products is in a good category, although several indicators are in the sufficient category. Keywords.    Musharakah Mutanaqisah (MMQ), Take Over Financing, Shariah Home Financing.